Anthropometric characteristics, upper-body strength, and sprint paddling performance in competitive surfers - Sheppard, J. M.; Osborne, M.; Chapman, D.; Andrews, M. (Journal of Australian Strength and Conditioning, 2012)
The present study examined the potential differences in anthropometric characteristics, upper-body strength, and sprint paddling performance between youth and senior competitive surfers. Twenty competitive male surfers (19.1±6.8 years, 168.2±11.3 cm, 61.7±13.6 kg) were assessed for stature, mass, arm-span, sum 7 site skinfold thickness, Lean-Mass Ratio (LMR, sum 7 site skinfold/kg body-mass), pronated pull-up 1 repetition maximum (1 RM) and sprint paddling performance from a stationary start to 15 m. Independent t-tests were used to compare potential differences between youth (n:10) and senior group (n:10) of competitive surfers, with Cohen`s Effect Size (d) applied to reflect the magnitude of any differences observed. Senior surfers were not different from youth surfers for sum 7 site skinfold thickness, yet had greater stature (p<0.001, d=2.7) and mass (p<0.001, d=2.8). Consequently, the composite lean mass ratio (body-mass/sum 7 site skinfold thickness, LMR) was greater (p=0.001, d=1.7) in senior competitive surfers. The senior surfers were faster in the 0-15 m sprint paddle test (p<0.001, d=2.9), possessed higher peak paddling velocity (p<0.001, d=2.3) and had greater absolute 1 RM pull-up strength (p<0.001, d=2.8) and 1 RM pull-up strength relative to body-mass (1 RM pull-up mass/subjects body-mass) (p<0.001, d=2.2). The results of this study suggest that practitioners working with competitive surfers should consider the importance of sprint paddle performance in surfers, and the need to optimize lean mass and relative strength, as these factors appear to distinguish between surfers of higher and lower athletic development and competitive level in the surfing population.